Characteristics of physical and chemical properties, antioxidant, antimutagenic and reparative activity of nanocomplexes of curcuminoids with cyclodextrins - M. A. Kapustin; A. S. Chubarova; I. V. Rzhepakovsky; S. I. Piskov; I. A. Evdokimov; A. D. Lodygin; V. G. Cigankov; N. V. Dudchik; A. V. Adamovich; V. P. Kurchenko (Современная наука и инновации)
The spectral properties and thermal stability of cyclodextrins:curcuminoids nanocomplexes were characterized by the use of the methods of IR spectroscopy and thermal analysis. The changes in the activation energy of thermal destruction of curcuminoids during the formation of nanocomplexes were calculated. In the model system for the reduction of the radical cation ABTS˙+, IC50 values were determined for nanocomplexes of curcuminoids with β-cyclodextrin (Curc:β-CD) and 2-hydroxypropyl-beta-cyclodextrin (Curc:HP-β-CD), obtained by co-evaporation and lyophilization at a ratio of 1:2, which were 1.076 g/L and 0.161 g/L, respectively. Using the Ames test, the presence of antimutagenic activity of the drugs Curc:β-CD and Curc:HP-β-CD was demonstrated. When Curc:HP-β-CD 1:2 nanocomplexes were added to the incubation medium of the drug, a significant decrease in the frequency of mutagenesis was observed by 50% compared to the control. The use of Curc:β-CD 1:2 nanocomplexes as a wound-healing agent on a skin patch wound model in Wistar rats showed the course of the regenerative process along the path of organotypic regeneration.